Successful Charge–Discharge Experiments of Anthraquinone-Bromate Flow Battery: First Report - Lilia Abunaeva; Natalia Kartashova; Kirill Karpenko; Dmitry Chikin; Darya Verakso; Pavel Loktionov; Roman Pichugov; Anatoly Vereshchagin; Mikhail Petrov; Anatoly Antipov (Energies, 2022)
The proposed anthraquinone-bromate cell combines the advantages of anthraquinone-bromine redox flow batteries and novel hybrid hydrogen-bromate flow batteries. The anthraquinone-2,7-disulfonic acid is of interest as a promising organic negolyte due its high solubility, rapid kinetics of electrode reactions and suitable redox potentials combined with a high chemical stability during redox reactions. Lithium or sodium bromates as posolytes provide an anomalously high discharge current density of order ~A cm−2 due to a novel autocatalytic mechanism. Combining these two systems, we developed a single cell of novel anthraquinone-bromate flow battery, which showed a power density of 1.08 W cm−2, energy density of 16.1 W h L−1 and energy efficiency of 72% after 10 charge–discharge cycles.